Konstruksi Skizofrenia dalam Video Klip Halu-Feby Putri - Muhammad Zahran Arrafi; Altobeli Lobodally (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Schizophrenia is a mental disorder that sufferers experience over a long period of time. Schizophrenia is the theme of the concept and theme in Feby Putri's video clip titled "Halu". The purpose of this study is to find out the construction of schizophrenia in the Halu - Feby Putri Video Clip using the paradigm of constructivism. This study uses the Theory of Social Media Mass Reality Construction and uses qualitative approach based on semiotic analysis using the meaning triangle of Charles Sanders Peirce, researchers use triangle of meaning namely sign, object, and intepretant. The study found that schizophrenia was constructed as an inability to control emotions, psychosis, impulses, hallucinations, behavioral instability, lack of confidence, emptiness, discomfort, hendaya to emotional thoughts, perceptions and behaviors, impaired concentration, emotional pain. Video clips can construct schizophrenia through every sign used inside.